2003
DOI: 10.1002/qre.535
|View full text |Cite
|
Sign up to set email alerts
|

Using Neural Networks to Detect and Classify Out‐of‐control Signals in Autocorrelated Processes

Abstract: This paper presents an artificial neural network model for detecting and classifying three types of non-random disturbances referred to as level shift, additive outlier and innovational outlier which are common in autocorrelated processes. To the best of our knowledge, this is the first time that a neural network has been considered for simultaneous detection and classification of such non-random disturbances. An AR (1) model is considered to characterize the quality characteristic of interest in a continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Woodall and Faltin [31] then gave a brief summary on the effect of autocorrelation on the performance of control charts and explained methods to deal with autocorrelation. Noorossana et al [23] presented an artificial neural network model for detecting and classifying three types of non-random disturbances referred to as level shift, additive outlier, and innovational outlier, which were common in autocorrelated processes. An autoregressive of order one, AR(1) model, was considered to characterize the quality characteristic of interest in a continuous process where autocorrelated observations were generated over time.…”
Section: The Effects Of Autocorrelation On X − Mr Control Chartmentioning
confidence: 99%
“…Woodall and Faltin [31] then gave a brief summary on the effect of autocorrelation on the performance of control charts and explained methods to deal with autocorrelation. Noorossana et al [23] presented an artificial neural network model for detecting and classifying three types of non-random disturbances referred to as level shift, additive outlier, and innovational outlier, which were common in autocorrelated processes. An autoregressive of order one, AR(1) model, was considered to characterize the quality characteristic of interest in a continuous process where autocorrelated observations were generated over time.…”
Section: The Effects Of Autocorrelation On X − Mr Control Chartmentioning
confidence: 99%
“…The first is their ability to detect correlations between subsets of the input signals, which is a problem that received the attention of many researchers [25,26]. The second aspect is the ability to model nonlinear relations between the monitored quality characteristics [25].…”
Section: Multivariate Neural Network Based Fault Recognitionmentioning
confidence: 99%
“…His results showed that BPN-based monitoring scheme performed better than residual control chart, X, EWMA, ARMAST control charts in major cases based on the in-control and out-of-control ARL performance. Noorsossana, Farrokhi, and Saghaei (2003) were the first to propose an NN model to detect and classify non-random disturbances in auto-correlated processes. Their experimental results showed that this NN model is an effective method for cause-selecting problems.…”
Section: Introductionmentioning
confidence: 99%